Silent brain infarcts impact on cognitive function in atrial fibrillation. (17th February 2022) - Kühne, Michael; Krisai, Philipp; Coslovsky, Michael; Rodondi, Nicolas; Müller, Andreas; Beer, Jürg H; Ammann, Peter; Auricchio, Angelo; Moschovitis, Giorgio; Hayoz, Daniel; Kobza, Richard; Shah, Dipen; et al.
Abstract: Aims: We aimed to investigate the association of clinically overt and silent brain lesions with cognitive function in atrial fibrillation (AF) patients. Methods and results: We enrolled 1227 AF patients in a prospective, multicentre cohort study (Swiss-AF). Patients underwent standardized brain magnetic resonance imaging (MRI) at baseline and after 2 years. We quantified new small non-cortical infarcts (SNCIs) and large non-cortical or cortical infarcts (LNCCIs), white matter lesions (WML), and microbleeds (Mb). Clinically, silent infarcts were defined as new SNCI/LNCCI on follow-up MRI in patients without a clinical stroke or transient ischaemic attack (TIA) during follow-up. Cognition was assessed using validated tests. The mean age was 71 years, 26.1% were females, and 89.9% were anticoagulated. Twenty-eight patients (2.3%) experienced a stroke/TIA during 2 years of follow-up. Of the 68 (5.5%) patients with ≥1 SNCI/LNCCI, 60 (88.2%) were anticoagulated at baseline and 58 (85.3%) had a silent infarct. Patients with brain infarcts had a larger decline in cognition [median (interquartile range)] changes in Cognitive Construct score [−0.12 (−0.22; −0.07)] than patients without new brain infarcts [0.07 (−0.09; 0.25)]. New WML or Mb were not associated with cognitive decline. Conclusion: In a contemporary cohort of AF patients, 5.5% had a new brain infarct on MRI after 2 years. The majority of these infarcts was clinically silent and occurred in anticoagulated patients. Clinically, overt and silent brain infarcts had a similar impact on cognitive decline. Clinical Trial Registration: ClinicalTrials.gov Identifier: NCT02105844, https://clinicaltrials.gov/ct2/show/NCT02105844 Structured Graphical Abstract: Structured Graphical Abstract Brain damage and change in cognitive function in patients with atrial fibrillation.